DINAMIKA EKONOMI ISLAM DI INDONESIA; Telaah Sosio-Historis Teologis Terhadap Bank Muamalat Indonesia - Mochamad Parmudi (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2016)
Bank Muamalat Indonesia (BMI with) is the symbol of the birth of the new banking system (GLBT) which gives the alternative regarding financial management in accordance with the Islamic Sharia. The establishment of the theological orientation in addition to BMI, also can not be separated from the calculation (rationality) behavioral economics. In terms of BMI is as an expression of the orientation of worldliness that is powerful enough to provide a secure banking system options.Analysis using qualitative methods of descriptive-i.e. not limited to at the level of the collection and compiling of data only. But includes also interpretations as to the meaning of the data obtained in an effort to elucidate the socio historical theological against BMI. Thus, BMI as a manifestation of a very important theological orientation, just as important as when the Muslims consider the manifestation of religious orientation embodied in the form of ritual piety (eg: build the mosque, went on Hajj, and so forth). So, in this context the presence of BMI in sociological proves the existence of close relationships (positive correlation) between the doctrines of religion with the actions/behavior of the economic life of the Muslims.